2021
DOI: 10.3233/jad-210231
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic Perspectives on Parkinson’s Disease Care and Research Participation

Abstract: Background: Hispanics are under-represented in Parkinson’s disease (PD) research despite the importance of diversity for results to apply to a wide range of patients. Objective: To investigate the perspective of Hispanic persons with Parkinson disease (PWP) regarding awareness, interest, and barriers to participation in research. Methods: We developed and administered a survey and qualitative interview in English and Spanish. For the survey, 62 Hispanic and 38 non-Hispanic PWP linked to a tertiary center were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Additional reasons limiting recruitment also included language barriers and potential financial burden. 24 Similar evidence has also been descried in other subspecialties. Non-White participants in 2 oncology clinics were less likely to gather clinical trial information from physicians or from the internet when compared with White individuals and more likely to believe that they had been treated in clinical trials without their knowledge, 25 reflecting the true experience of marginalized racial and ethnic groups in recent times.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Additional reasons limiting recruitment also included language barriers and potential financial burden. 24 Similar evidence has also been descried in other subspecialties. Non-White participants in 2 oncology clinics were less likely to gather clinical trial information from physicians or from the internet when compared with White individuals and more likely to believe that they had been treated in clinical trials without their knowledge, 25 reflecting the true experience of marginalized racial and ethnic groups in recent times.…”
Section: Discussionsupporting
confidence: 74%
“…21,22 Previous studies have also reported that patients belonging to marginalized racial and ethnic groups may be less well informed about or aware of clinical trials. 23,24 For instance, a recent study evaluating the willingness of Hispanic individuals with PD to participate in clinical trials revealed that the lack of awareness regarding PD research remained a significant obstacle. Additional reasons limiting recruitment also included language barriers and potential financial burden.…”
Section: Randomized Participants 336 298mentioning
confidence: 99%
“…As with many research studies, the higher rates of white and highly educated respondents likely bias the outcomes. Little is known about the disease features and specific needs of non-White ethnoracial groups, [26][27][28] LGBTQ+ populations, and people from lower socioeconomic levels and without high levels of education. People with LBD from underrepresented groups may be at a higher risk of misdiagnosis, and likely to have even less access to education, research participation, and clinical resources.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…As a research community, we need to prioritize inclusivity and devote the necessary resources and funds to tackling this problem. Strategies may include partnering with trusted community organizations and advocates, providing study materials in languages other than English, ensuring a diverse research team [ 68 ], providing training on inclusive research practices [ 93 •], educating community providers on research opportunities [ 96 ], and providing the technology required for participation. We cannot assume that recruitment strategies designed for traditional in-person studies will translate to decentralized studies [ 76 ].…”
Section: Researchmentioning
confidence: 99%